Modeling energy scenarios for the implementation of wind energy facilities: R3EA Project - Meireles, M.; Max López-Maciel; Fátima Lima; Edimar Ramalho; André Oliveira; José Villar; Madaleno, M.; Marta Ferreira Dias; Alves, M. R. (Proceedings of the 6th International Conference on Energy and Environment (ICEE 2024): Bringing Together Engineering and Economics, 2024)
Portugal’s electricity generation is characterized by its renewable matrix, with the contribution of high shares of hydropower, wind, and, more recently, solar power, which accounted for 56% of the country's electricity production in 2020. The Portuguese government has set ambitious targets for renewable energy development in 2030. In that sense, the R3EA project (https://r3ea.web.ua.pt/pt/projeto) for the “Economic and Externalities valuation of renewable energies in Portugal” aims to contribute towards the assessment of the impact of new investments in solar and wind electricity generation capacity in the Centro Region of Portugal. The main contribution is a global impact assessment, not only from the traditional perspective of energy generation planning, but also considering the costs and benefits (externalities) associated with these investments. As such, the R3EA project contributes towards discussing the current situation of wind and energy energy deployment, with a specific focus on the definition of energy scenarios for future investments in wind energy facilities for the Centro Region of Portugal, looking to integrate sustainability dimensions. Although R3EA studies both wind and solar, this study will consider the wind only in its analysis. In this context, this study promotes a preliminary assessment of the wind power profile and a scenario for the case of Portugal. Expected results should guide regulatory decisions at the national and regional levels in energy policy